(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Serrapeptase, a proteolytic enzyme, has been used for the adjuvant treatment of many diseases. However, its fibrinolytic activity is still uncertain. Herein, the fibrinolytic activity of serrapeptase and its in vitro thrombolytic effects were investigated. The results showed that the fibrinolytic activity of serrapeptase was 1295 U/mg, and the specific activity was 3867 U/mg of protein when its proteolytic activity toward casein was 2800 U/mg. The optimum temperature and pH for serrapeptase activity were 37-40°C and 9.0, respectively. At 1 mmol/L, Zn2+, Mn2+ and Fe2+ could activate the fibrinolytic activity of serrapeptase, while K+, Cu2+, sodium dodecyl sulfate (SDS) and ethylene diamine tetraacetic acid (EDTA) inhibited it. In vitro tests showed that serrapeptase could completely prevent blood coagulation at 150 U/mL, and the percentage of blood clot lysis reached 96.6% at 37°C after 4 h at 300 U/mL. These results indicate that serrapeptase has excellent fibrinolytic activity, and can be used as a health food or candidate drug for the prevention or treatment of thrombotic diseases.